2010
DOI: 10.1007/s10533-010-9446-1
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency monitoring of phytoplankton dynamics within the European water framework directive: application to metalimnetic cyanobacteria

Abstract: Large, sub-alpine, stratified lakes are directly within the scope of the European Water Framework Directive (WFD) and need adapted monitoring systems. Moreover, anthropogenic eutrophication was frequently the main cause of their water quality degradation in the 20th century. This paper is primarily aimed at demonstrating how in situ sensor-equipped buoys could be the base of monitoring designs to support the WFD objectives. The core of this paper, mainly methodological, focuses on single-depth, high frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 50 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…At the horizontal scale, there was contrast between P. rubescens biomasses in the northern and southern parts of the lake, that is, when high biomasses were found in the northern part, low biomasses were present in the southern part, and vice versa. We also found that the effect of internal waves persisted for several days after the end of a high-wind event, and this has been confirmed by recent data obtained by a buoy equipped with various different sensors (Le Vu et al, 2010) showing that internal waves can be detected throughout the stratified period of the water column. This finding suggests that P. rubescens is subjected to the impact of seiches throughout its development in the metalimnic layer from the lake from April to late September.…”
Section: Discussionsupporting
confidence: 86%
“…At the horizontal scale, there was contrast between P. rubescens biomasses in the northern and southern parts of the lake, that is, when high biomasses were found in the northern part, low biomasses were present in the southern part, and vice versa. We also found that the effect of internal waves persisted for several days after the end of a high-wind event, and this has been confirmed by recent data obtained by a buoy equipped with various different sensors (Le Vu et al, 2010) showing that internal waves can be detected throughout the stratified period of the water column. This finding suggests that P. rubescens is subjected to the impact of seiches throughout its development in the metalimnic layer from the lake from April to late September.…”
Section: Discussionsupporting
confidence: 86%
“…As a matter of consequence, many efforts have been made to develop and validate new innovative devices for the survey of cyanobacterial blooms. For example, probes equipped with chlorophyll-a/phycocyanin and other sensors that can be coupled with autonomous monitoring platforms are now available for punctual or continuous estimations of cyanobacteria biomasses in the water column [ 6 , 7 ]. In the same way, the use of remote sensing [ 8 ] and LIDAR [ 9 ] allows to estimate the horizontal and/or vertical distribution of the cyanobacterial biomass in a lake.…”
Section: Introductionmentioning
confidence: 99%
“…AHFM systems can assist in managing the provisioning of clean water in several ways (Table ). In water supply schemes, AHFM has been used to avoid the withdrawal of water rich in nutrients, sediment, metals and organic matter during floods , or from anoxic layers; the detection of organic matter, the presence of which leads to formation of disinfection byproducts during chlorination; and the identification and prediction of harmful cyanobacterial blooms . The information delivered by AHFM is used in different ways to assist management: it may be used to prompt grab sampling for confirmation of a threat, to switch to alternative unpolluted sources, to trigger an in situ remediation action (e.g., application of hydrogen peroxide for algal bloom control or to change the intake depth in reservoirs with several withdrawal structures).…”
Section: Ahfm For Maximizing the Provision Of Ecosystem Services Supp...mentioning
confidence: 99%
“…Assessments of ecological status based on other variables, particularly dissolved oxygen concentration, can also be misleading unless AHFM is applied . In fact, ecological assessment using AHFM of chlorophyll a and cyanobacterial pigments is already in use in some countries …”
Section: Ahfm For Evaluating the Ecological Status According To The Wfdmentioning
confidence: 99%
See 1 more Smart Citation